Editorial - Fonseca, Fernanda Padovesi (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2015)
In this issue, the GEOUSP publishes articles that reiterate diversity as brand repertoire of geographical science and thus maintains its stance of embracing this plurality, which expresses the possibilities of research, analysis and interpretation of all forms of production of human space (at all scales), whether urban, rural or natural. How could it be, this perspective opens up the mológicas epistemological issues and developments of new research in the universe of our education systems